Development and productivity of two beet genotypes for fertilization - Silveira, Daniel Mocelin; Carvalho, Flávio Corrêa de; Mariano, Gustavo Pailo; Francisco, André Luiz Oliveira de (Scientia Agraria Paranaensis, 2020)
Beet needs a high demand of nutrients to improve its development and productivity. The objective of this work was to evaluate the effect of fertilizer forms in the development and productivity of the beet crop. The experiment was carried out in the experimental area of the Fazenda Escola of the Higher Education Center of Campos Gerais, located in the city of Ponta Grossa-PR, between September and November 2018. The experimental design was randomized blocks in a 2x4 factorial scheme [2 genotypes of beet (Boron hybrid and Tall Top Early Wonder cultivar) x 4 forms of fertilization, T1 - control (without fertilization), T2 - poultry litter, T3 - bovine manure and T4 - NPK], containing four repetitions. The harvest was carried out at 75 days after transplanting the seedlings, harvesting five plants from each plot to carry out the analyzes, thus evaluating the number of leaves per plant, height of the aerial part, fresh mass of the aerial part and the root, productivity, horizontal diameter and commercial classification of root, presence of white rings through notes and soluble solids content (ºBrix). Among the different genotypes studied, the cultivar Tall Top Early Wonder was superior in the variables of plant height, fresh mass of roots and leaves and soluble solids, 75 days after transplantation. The cultivar Tall Top Early Wonder responded better, implying the idea that organic fertilization would be an alternative as a source of nutrients in beet production.